2014
DOI: 10.1016/j.biomaterials.2014.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Micro-scale and meso-scale architectural cues cooperate and compete to direct aligned tissue formation

Abstract: Tissue and biomaterial microenvironments provide architectural cues that direct important cell behaviors including cell shape, alignment, migration, and resulting tissue formation. These architectural features may be presented to cells across multiple length scales, from nanometers to millimeters in size. In this study, we examined how architectural cues at two distinctly different length scales, “micro-scale” cues on the order of ~1–2 μm, and “meso-scale” cues several orders of magnitude larger (>100 μm), int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 54 publications
3
59
0
Order By: Relevance
“…However, initial cell seeding density in that study was 10-fold lower than the current study, and cells were not confluent on the surface of the scaffolds after 28 days of culture. Emerging evidence suggests that response to microarchitectural cues, cell proliferation, migration, symmetry of cell-cell contacts, and direction of cellular and matrix alignment are tightly coordinated [6165]. In the initial period after seeding on electrospun fibers, MSCs demonstrate potent directionality in their migration response and in their cell-cell contacts on aligned compared to nonaligned electrospun fibers [66].…”
Section: Discussionmentioning
confidence: 99%
“…However, initial cell seeding density in that study was 10-fold lower than the current study, and cells were not confluent on the surface of the scaffolds after 28 days of culture. Emerging evidence suggests that response to microarchitectural cues, cell proliferation, migration, symmetry of cell-cell contacts, and direction of cellular and matrix alignment are tightly coordinated [6165]. In the initial period after seeding on electrospun fibers, MSCs demonstrate potent directionality in their migration response and in their cell-cell contacts on aligned compared to nonaligned electrospun fibers [66].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated tendon gene expression from cells cultured on fibrous scaffolds where tendon gene expression was not significantly altered, although this was a comparison between aligned and random scaffolds [37]. In another study, Gilchrist et al compared aligned (parallel) and grid (perpendicular) architectural cues and observed an increase of gene expression of SCX and COL I from day 6 to day 12, with no significant differences in tendon gene expression between designs [22], similar to results observed in our scaffolds. Our findings suggest that alignment, rather than orientation, may be the predominant cue influencing tenogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, micro-gels that are guided by magnetic forces to assemble much like Tetris blocks have recently been introduced, in order to achieve higher-order multi-component tissues (3). Competing cues at different scales will likely also add complexity in the 3D situation, as has been observed in 2D (69). Overall, the need for architecturally controlled multilayered tissues represents a great challenge for tissue patterning and architectural engineering in the future.…”
Section: Challenges For the Futurementioning
confidence: 93%